2015
DOI: 10.1016/j.mib.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Translational deficiencies in antibacterial discovery and new screening paradigms

Abstract: An impending disaster is currently developing in the infectious disease community: the combination of rapidly emerging multidrug-resistance among clinically-relevant bacterial pathogens, together with an unprecedented withdrawal from industrial dedication to this disease area, is jeopardizing human health on a societal level. For those who remain focused and dedicated to identifying solutions to this growing problem, additional challenges await when in vitro activity does not correlate with in vivo efficacy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…To this end, screens for antibacterial agents are increasingly being developed with the goal of mimicking the environment of the sites of infection . The impetus for this stems from the growing appreciation that conventional laboratory media does not accurately represent conditions encountered by bacterial pathogens in the host . Further, chemical collections used to find leads for new antibacterial drugs have been exhaustively screened via the traditional route, and chances for new discoveries are low.…”
mentioning
confidence: 99%
“…To this end, screens for antibacterial agents are increasingly being developed with the goal of mimicking the environment of the sites of infection . The impetus for this stems from the growing appreciation that conventional laboratory media does not accurately represent conditions encountered by bacterial pathogens in the host . Further, chemical collections used to find leads for new antibacterial drugs have been exhaustively screened via the traditional route, and chances for new discoveries are low.…”
mentioning
confidence: 99%
“…Due to the rapidly growing bacterial antibiotic resistance and the lack of novel antibiotics reaching the market, bacterial infections are still a severe global problem. Therefore, exploring new types of antibacterial drugs with a novel mechanism or chemical structure is urgently needed . With these novel compounds in hand, we thus set out to study the antimicrobial activities preliminarily in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In tuberculosis research, this is especially relevant, as it has been shown that M. tuberculosis responds differently to treatment intracellularly inside macrophages, in comparison to standard (extracellular) in vitro experiments without macrophages. 8,9 Moreover, the interaction among pathogen, immune response, and treatment might be more relevant to study in the zebrafish, as it shows granuloma formation upon infection, 10 which is not observed in the mouse, the standard preclinical organism in tuberculosis research. 11 Translation of pharmacological findings from zebrafish embryos to higher vertebrates, including humans, requires a quantitative understanding of similarities and differences in pathophysiology between infecting mycobacteria.…”
Section: What Does This Study Add To Our Knowledge?mentioning
confidence: 99%
“…For each strain, three biological replicates from individually grown colonies were collected in individual tubes per time point, with a start inoculum at OD 600 of 0.05, approximating 1× 10 6 CFU/ mL. At different time points (0, 8,11,18,23,28,36,42,49,56,64,69,77,85,92,112,114, and 221 days), the viability of the cultures, defined as CFUs per mL, was determined by plating a series of 10-fold dilutions (ranging from 1:10 to 1:1,000,000) in triplicate on Difco Middlebrook 7H10 agar (BD Biosciences) containing 5% glycerol (Sigma-Aldrich, Saint Louis, MO) and 10% BBLTM Middlebrook Oleic Albumin Dextrose Catalase Enrichment (BD Biosciences).…”
Section: Total Bacterial Count Assaymentioning
confidence: 99%
See 1 more Smart Citation